University students’ perspectives on creativity in learning in the 21st century - Sitorus, Jonni (Creativity Studies, 2025)
The importance of students’ creativity in tertiary institutions lies in the need to prepare young people for the 21st century. On the other hand, higher education is generally unfamiliar with creativity environments, so it will hinder their learning creativity outcomes and experiences, which will impact their creativity cognition and knowledge. The research goals are to calculate the percentages of university students’ perspectives on the importance of their learning creativity outcomes and experiences and to test the influence of each variable. All respondents are 586, with an age range of 19–24 years. The author created learning creativity instruments. The results showed that there are twelve outcomes and eleven experiences of learning creativity that are important to university students. Less than 50% of university students get learning creativity experiences on campus four or more times a week and/or for more than three hours a day. There is a positive and significant influence between the importance of learning creativity outcomes and experiences as well as the frequency and duration of those experiences. For achieving twelve learning creativity outcomes, tertiary institutions must ensure the implementation of experiences learning creativity experiences, as well as the adequacy of the frequency and duration of those experiences.